An Economic Theory of Education Externalities: Effects of Education Capital - HARASHIMA, Taiji (Journal of Research in Educational Sciences; Vol 12 No 14 (2021): JRES, Volume XII, Issue 14, 2021DO - 10.14505/jres.v12.14.01, 2021)
The source of education externalities has been mostly explained based on the concept of human capital, but this concept is very elastic, so the mechanism behind education externalities has not necessarily been sufficiently explained theoretically. In this paper, I construct a model of education externalities based on the concept of education capital, and show that it is education capital, not human capital, that generates education externalities. Unlike human capital, the effects of education capital have upper bounds because there is a division of labor (i.e., there are specialists). The uncovered mechanism of education externalities has the potential to provide many valuable insights for educational institutions and policy. For example, elementary schools should basically be compulsory, but whether education (not research) in universities should be subsidized by governments may depend on the degree of generosity of high-income people.